Projecting Podocarpaceae response to climate change: we are not out of the woods yet - Twala, Thando C.; Fisher, Jolene T.; Glennon, Kelsey L. (Oxford University Press, 2023)
Under the changing climate, the persistence of Afrotemperate taxa may be threatened as suitable habitat availability decreases. The unique disjunct ranges of podocarps in southern Africa raise questions about the persistence of these species under climate change. Here, we identified likely environmental drivers of these distributions, characterized the current and future (2070) environmental niches, and projected distributions of four podocarp species in South Africa. Species distribution models were conducted using species locality data for Afrocarpus falcatus, Podocarpus latifolius, Pseudotropheus elongatus and Podocarpus henkelii and both historical climate data (1970–2000) and future climate scenarios (Representative Concentration Pathway [RCP] 4.5 and 8.5, 2061–2080) to estimate the current and future distributions. We also used this opportunity to identify the most important climatic variables that likely govern each species’ distribution. Using niche overlap estimates, a similarity test, and indices of niche expansion, stability and unfilling, we explored how niches change under different climate scenarios. The distribution of the study species was governed by the maximum temperature of the warmest month, temperature annual range, mean temperature of the wettest quarter, and precipitation of the wettest, driest and warmest quarters. The current distribution of A. falcatus was predicted to expand to higher elevations under RCP 4.5 and RCP 8.5. Podocarpus henkelii was predicted to lose most of its suitable habitat under RCP 4.5 and expand under RCP 8.5; however, this was the opposite for P. elongatus and P. latifolius. Interestingly, P. elongatus, which had the smallest geographic distribution, showed the most vulnerability to climate change in comparison to the other podocarps. Mapping the distribution of podocarps and understanding the differences in their current and future climate niches provide insight into potential climate drivers of podocarp persistence and the potential for adaptation of these species. Overall, these results suggest that P. elongatus and P. henkelii may expand to novel environmental niches.
Keywords: Climate change; Environmental niche; Persistence; Podocar; Species distribution; SDG-13: Climate action; SDG-15: Life on land